Factors Associated With Weight Management Referral Acceptance and Uptake in Kidney Transplant Candidates - Linda‐Marie Lavenburg; Harry Morford; Susan Stark; Sanjana Kamat; Mariela Sierra Mendoza; Michele Molinari; Chethan Puttarajappa (Clinical Transplantation, 2026)
ABSTRACT Introduction Obesity is a significant barrier to kidney transplantation (KT). KT candidates with obesity are often referred to weight management programs (WMP) but patients' acceptance for WMP referral and their subsequent follow‐through are unknown. Design and Methods Using a single‐center study, we evaluated the effectiveness of referrals to medical or surgical WMPs among KT candidates to initiate obesity care. We examined factors associated with patients establishing care and any effects of referral acceptance on BMI, KT waitlisting and transplantation. Results The median age was 57 years, 49% were male, 56% were White, 79% were on dialysis, and 53% were from high social disadvantage areas. Thirty patients (50.8%) accepted WMP referral but only 9 (15.3%) contacted WMP. Patients accepting referral had higher BMI [median 47 vs. 45; p = 0.002] and resided closer to the KT center [20 vs. 48 miles; p = 0.010]. In multivariable models, referral acceptance decreased 2% with each mile away from KT center (OR 0.98; 95%CI: 0.96–1.00) and increased by 22% with every 1 unit increase in BMI (OR 1.22, 95%CI: 1.03–1.45). Among patients accepting referral, every 1‐year increase in age reduced odds of contacting WMP by 17% (OR 0.83, 95%CI: 0.74–0.96). Conclusion A large share of KT candidates with obesity do not establish care with WMPs. Increasing age and distance to KT center were contributing factors to low referral acceptance and engagement. Efforts aimed at obesity management in KT should consider these barriers. WMPs integrated within KT programs may overcome barriers to establishing care with WMPs.